Structural Behaviour of Reinforced Concrete Beams Made of Selected Waste Glass and Ceramic Tiles - Abubaker M Alamleeh; Stanley M Shitote; Timothy Nyonboi (International Journal of Sustainable Construction Engineering and Technology, 2024)
Worldwide, construction and demolition wastes contribute the most wastes. Hence, environmental concerns have been raised, and more investigations have been recommended for recycling potential. Glass and Ceramic wastes are currently disposed of in landfills. This paper aims to study the structural behaviour of non-conventional concrete made of waste glass and ceramic tiles. A comparison is conducted between the normal and non-conventional concrete beams. The non-conventional concrete is made by replacing normal sand and gravel at 25% and 50% percentages. Both glass and ceramic tiles are used separately and blended in three different types (A, B, & C) of concretes. The laboratory experiments are verified with a Finite Element model for the three reinforced concrete types using ANSYS software. The results of conducted comparison shown that the non-conventional reinforced concretes have acceptable consistent with the normal reinforced concrete, and the reuse of glass and ceramic waste is technically feasible.